2020
DOI: 10.1186/s12884-020-02936-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of asymptomatic bacteriuria and sterile pyuria among antenatal attendants in hospitals in northern Ghana

Abstract: Background: Asymptomatic bacteriuria (ASB) and sterile pyuria (SP) are complexities of UTI whose prevalence are not known in the northern sector of Ghana. Our aim was to determine the occurrence of sterile pyuria and asymptomatic bacteriuria among pregnant women accessing antenatal care at a secondary and tertiary care hospitals in Tamale, northern Ghana. Methods: A cross sectional study was conducted by screening 530 pregnant women with no signs of acute urinary tract infection attending antenatal clinic for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The ASB proportion in the present study was lower compared to some earlier studies from sub-Saharan Africa, citing proportions of 7–40% [ 17 , 22 – 24 ], but it was comparable to those reported elsewhere (range 1.9–9.5%) [ 25 , 26 ]. The presently lower proportions of ASB may be related to the stringent definition, i.e.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The ASB proportion in the present study was lower compared to some earlier studies from sub-Saharan Africa, citing proportions of 7–40% [ 17 , 22 – 24 ], but it was comparable to those reported elsewhere (range 1.9–9.5%) [ 25 , 26 ]. The presently lower proportions of ASB may be related to the stringent definition, i.e.…”
Section: Discussionsupporting
confidence: 63%
“…The presently lower proportions of ASB may be related to the stringent definition, i.e. including only Enterobacterales as significant organisms, whereas in most other studies with higher ASB proportions, Staphylococci represented a substantial number of cases [ 17 , 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important difference between urine samples and other clinical samples (such as blood) in the diagnosis of pathogens is the need for specific quantification when diagnosing a case of UTI. Previous studies reported that bacterial loads below 10 5 CFU/mL were considered to be UTInegative while bacterial loads above 10 5 CFU/mL were considered to be UTI-positive or diagnosed as having significant bacteriuria (Hansen et al, 2013;Belete et al, 2019;Gebremariam et al, 2019;Karikari et al, 2020). Other studies opted to use lower colony counts of >10 4 CFU/mL as an indicator of significant bacteriuria (Milovanovic et al, 2019;Schuh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic bacteriuria is the presence of bacteria in the urine of an individual that does not have symptoms and signs of urinary tract infection, provided that the urine was collected without contamination [6][7][8][9] . Patients with asymptomatic bacteriuria show no obvious symptoms and appear clinically normal.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with asymptomatic bacteriuria show no obvious symptoms and appear clinically normal. Several researches have been conducted on asymptomatic bacteriuria in varying age-groups and cohorts [6][7][8][9] . Delzell and Lefevre 6 documented a global prevalence of 2 -10%.…”
Section: Introductionmentioning
confidence: 99%